2019
DOI: 10.1111/pin.12870
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow niches in myeloid neoplasms

Abstract: Pathological phenotypes of myeloid neoplasms are closely related to genetic/chromosomal abnormalities of neoplastic cells whereas the bone marrow microenvironment, including stromal elements and hematopoietic stem cell niche cells, have a great influence on the differentiation/proliferation of both hematopoietic and neoplastic cells. The pathology of myeloid neoplasms might be generated through the interaction of hematopoietic (stem) cells and stromal cells. The present study aims to provide the morphological/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The CXCL12 chemokine is constitutively released from bone marrow stromal cells and contributes to maintaining stem cells in bone marrow niches by binding to CXCR4 on CD34+/CD117 + hemopoietic progenitors and leukemic blasts too [ 16 ]. Therefore, CXCL12 may also be involved in protecting the leukemic stem cells and contributing to myelofibrosis progression [ 22 ], though CXCR4 is downregulated in the malignant progenitors, which may explain extramedullary clonal hematopoiesis in myelofibrosis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CXCL12 chemokine is constitutively released from bone marrow stromal cells and contributes to maintaining stem cells in bone marrow niches by binding to CXCR4 on CD34+/CD117 + hemopoietic progenitors and leukemic blasts too [ 16 ]. Therefore, CXCL12 may also be involved in protecting the leukemic stem cells and contributing to myelofibrosis progression [ 22 ], though CXCR4 is downregulated in the malignant progenitors, which may explain extramedullary clonal hematopoiesis in myelofibrosis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CXCL12 may also be involved in protecting the leukemic stem cells and contributing to myelofibrosis progression [ 22 ], though CXCR4 is downregulated in the malignant progenitors, which may explain extramedullary clonal hematopoiesis in myelofibrosis [ 41 ]. Endothelial cells may also express CXCL12, although at a lower level [ 16 ]. CXCL12 plays an essential role in stem cell homing at transplantation and the CXCL12/CXCR4 interaction supports stromal cell resistance and restoration of the stromal network after myeloablative irradiation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDS is myeloid neoplasms characterized by clonal proliferation of hematopoietic stem cells, recurrent genetic abnormalities, ineffective hematopoiesis, peripheral-blood cytopenia, and a high risk of evolution to AML (1). Recent evidence has revealed that the bone marrow microenvironment (BMME), including mesenchymal stem cells and hematopoietic stem cell niche cells, is another key contributor to disease initiation and progression (2). Malignant clonal cells can modify the BMME via aberrant production of secreted factors, and the resulting dysfunctional BMME further promotes clonal expansion (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The bone marrow niche is defined as a local tissue microenvironment that maintains and regulates hematopoietic stem cells (HSCs). Many previous studies have suggested that mesenchymal stem cells (MSCs) and vascular endothelial cells maintain HSCs and regulate their proliferation and differentiation in the bone marrow niche [ 1 , 2 , 3 , 4 ]. The bone marrow niche has been rapidly elucidated in recent years by next-generation sequencing and cell analysis techniques [ 5 ].…”
Section: Introductionmentioning
confidence: 99%